Online student attendance monitoring system - Mahmud, Murni; Mustapha, Zatil Azyyati (IIUM Press, 2011)
The Online Student Attendance Monitoring System project is targeted for use at the Kulliyyah of Information and Communication Technology (KICT), HUM. This system is based around tracking student absenteeism. An attendance record is stored for a student only when he or she is absent. No record will be stored when a student is in attendance. This is the easiest approach in terms of record entry. The Online Student Attendance Monitoring System can only be managed and updated by administrators or lecturers of KICT once they enter their username and password. The students of KICT can access or view the information stored in the system to see their attendance status. This system can also be used to support and print attendance reports. While students and parents view only the concerned students' attendance, lecturers and Dean have access to the entire statistics of class attendance. This chapter will discuss the development of the Online Student Attendance Monitoring System and its implementation in brief.